Young or adult users of multiple tobacco/nicotine products urgently need to be informed of meaningful differences in product risks. (January 2018) - Kozlowski, Lynn T.; Sweanor, David T.
Abstract: Previously, it has been argued that health information efforts need to inform the public about meaningful differential risks from tobacco/nicotine products. The fact of multiple product use by the same individual further supports this need. When the majority of youth, for example, who use smokeless tobacco are also current tobacco smokers, it makes little sense to mount a smokeless prevention campaign that fails to include clear messages about the much greater risks from smoking. In April 2016, The Food & Drug Administration (FDA) announced a 36 million campaign for youth that "smokeless doesn't mean harmless." Research shows the public (a) already knows that smokeless tobacco is not harmless, but are (b) also largely unaware that cigarettes are much more harmful than smokeless. Though not harmless, smokeless tobacco has been estimated to be over 90% less harmful than cigarettes. 'Gateway' fears are made moot by current use of multiple tobacco/nicotine products. When multi-tobacco product use is commonplace among users, usable information on significant differences in risk is crucial for both adult and younger users. The FDA and like campaigns and health information websites should follow established ethical principles and accepted communication methods to inform the public of less-harmful tobacco/nicotine products as well as the greater harms of smoking, in keeping with the Surgeon-General's advice that reductions in smoking in particular will bring about the greatest public health advances.